Effect of Intellectual Capital on the Performance of Banking Companies Listed on the Indonesian Stock Exchange - Rahmi, Rachmi Saputri; Zulvia, Yolandafitri (Financial Management Studies, 2024)
This study aims to analyze the effect of intellectual capital and its components, namely research capital employe, human capital, and structural capital on company performance both accounting performance and market performance. This study also uses control variables in the form of company size. This study uses all banking companies listed on the Indonesia Stock Exchange as the population. Sampling was carried out using purposive sampling method, with the sample criteria publishing the company’s annual report for three consecutive years from 2020-2022. The analysis method used is multiple linear regression analysis using the IBM SPSS Statistics 26 program. The results of this study concluded that intellectual capital, employee capital, human capital have a positive and significant effect on accounting-based performance and market-based performance. While structural capital has no significant effect on accounting-based performance or market-based performance in banking companies listed on the Indonesia Stock Exchange.